2022
DOI: 10.2500/aap.2022.43.220022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough in asthma is associated with increased airway inflammation, more comorbidities, and worse clinical outcomes

Abstract: Background: Cough is often the most prominent and intractable symptom reported by patients with asthma, but few studies have explored the characteristics of patients with asthma and with chronic cough (CC) in a real-world setting. Methods: In a prospective cohort study, patients ages ≥ 18 years with stable asthma were consecutively recruited at the West China Hospital, Sichuan University. The patients were classified as having asthma with CC (the CC group) or asthma with non-CC (the non-CC group) after 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In this observational study, increased sputum eosinophilic inflammation was found in the CC group compared with the non-CC group. Our recently published study found that asthma patients with CC had elevated airway inflammation [ 14 ]. But M arsden et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this observational study, increased sputum eosinophilic inflammation was found in the CC group compared with the non-CC group. Our recently published study found that asthma patients with CC had elevated airway inflammation [ 14 ]. But M arsden et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cough severity and cough-related quality of life were assessed using a cough symptom score [ 14 ], cough VAS [ 22 ] and the Chinese version of the Leicester Cough Questionnaire (LCQ) [ 23 ]. The LCQ consists of 19 questions that cover three subdomains reflecting physical, social and psychological issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cough is a major symptom during asthma exacerbation causing severe distress, but has not been well investigated for its clinical relevance in the context of severe asthma. 46 80 81 Cough is more frequent in severe asthma than in non-severe asthma and associated with worse health-related QoL and asthma control. 81 Mechanisms underlying cough may overlap with, but are distinct from those of wheezing or breathlessness.…”
Section: The Concept Of Treatable Traits In Severe Asthmamentioning
confidence: 99%
“… 46 80 81 Cough is more frequent in severe asthma than in non-severe asthma and associated with worse health-related QoL and asthma control. 81 Mechanisms underlying cough may overlap with, but are distinct from those of wheezing or breathlessness. However, as cough is not included in current asthma assessment tools, such as ACT or ACQ, poorly controlled cough often misguides clinicians to step up in asthma therapy.…”
Section: The Concept Of Treatable Traits In Severe Asthmamentioning
confidence: 99%